(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Surface water and sediment samples were collected from various sampling sites surrounding the ship building industries in Goa region and plated on Zobell’s marine agar, Nutrient agar and mineral salt medium (MSM) containing tributyltin chloride (TBTC) 0.1mM. The physico-chemical characteristics of the environmental samples were determined. The total viable counts of bacteria in the medium with TBTC ranged from 8 × 102 - 40 × 106 cfuml. The predominant bacterial colonies were isolated, purified and screened for TBTC tolerance studies. Amongst these, two bacterial strain tolerated 7mM TBTC and showed prominent growth in MSM with 5 mM TBTC. Based on morphological, biochemical, molecular characteristics and phenogram, the isolate was grouped under Alcaligenes sp.